(untitled) (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: This study investigated the comparative morphological analysis of the vomeronasal organ and the accessory olfactory bulb in dogs and rabbits. Materials and Methods: A total of 15 heads obtained from each adult healthy Balady dog (Canis familiaris) and New Zealand rabbit (Oryctolagus cuniculus) of both sexes. The animals were sedated and anesthetized. Then, the heads were removed for computing topography, gross, and cross-sectional anatomy and histological techniques. Results: The vomeronasal organ was blind bilateral tubes enclosed by J-shaped cartilage on each side of the nasal septum. In dogs, it extended from the level of the upper third premolar teeth to the third incisive teeth. While in rabbits, it had no relation with the upper teeth. In cross section, the vomeronasal organ was pear-shaped in dogs and oval in rabbits. The accessory olfactory bulb was a small oval-shaped in dogs, but larger and ovoid in rabbits with clear lamination in its structure. The vomeronasal epithelium in rabbits was higher in its thickness than that of the dog. The vomeronasal duct had medial sensory and lateral respiratory epithelium. The vomeronasal glands were voluminous and of serous type in rabbits other than were seromucous in dogs. Conclusion: The most characteristic structural variations achieved in the vomeronasal organ and the accessory olfactory bulb of the dog and rabbit gave an indication that the organ was more functional in rabbits than in dogs. The detection and response to the pheromonal stimuli were referred to as the occurrence of olfactory epithelium in the vomeronasal organ. J. Adv. Vet. Anim. Res., 6(4): 506-515, December 2019